2020
DOI: 10.1111/jocn.15339
|View full text |Cite
|
Sign up to set email alerts
|

To explore the experience of research nurses who obtain consent from adults in emergency settings to participate in clinical trials, either prospectively or post enrolment

Abstract: Aim: To explore the understanding and experiences of research nurses who obtain informed consent from adult patients participating in emergency care research.Design: Qualitative phenomenographic descriptive study.Methods: Ten research nurses from six hospitals in England were recruited. Data were collected using semi-structured face-to-face and telephone interviews between January 2019 and March 2019. Interviews were transcribed verbatim and analysed thematically, informed by phenomenography. COREQ was followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 26 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Five studies reported the views of HCPs and researchers, finding largely positive views towards deferred consent which were consistent across the reported countries [ 24 , 27 , 31 , 40 , 42 ]. The level of research experience may influence HCPs’ and researchers’ views.…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…Five studies reported the views of HCPs and researchers, finding largely positive views towards deferred consent which were consistent across the reported countries [ 24 , 27 , 31 , 40 , 42 ]. The level of research experience may influence HCPs’ and researchers’ views.…”
Section: Resultsmentioning
confidence: 69%
“…The level of research experience may influence HCPs’ and researchers’ views. Interviews with UK research nurses found those with less experience viewed deferred consent as problematic and felt uncomfortable with the process, tending to avoid enrolling patients into trials when prospective written consent was not possible [ 27 ]. However, experienced nurses recognised the importance of deferred consent and felt more comfortable dealing with the challenges associated with the process [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations